Barriers and facilitators of bystander intervention in response to racism in Colombia - Minna Lyons; Gayle Brewer; Maria Ines Gandolfo Conceição; Ana Lucía Jaramillo-Sierra; Maria Fernanda Reyes-Rodriguez (Global Public Health)
Racial discrimination is a pervasive global problem. Bystanders who observe racism can intervene to support the targets of racism, but they often fail to do so due to several context-specific barriers. There is currently little research on bystander behaviour in racism outside of English-speaking countries. We used mixed methods to explore bystander responses to everyday racism in Colombia. In an online survey, participants (N = 1,157) were presented with a scenario where they observed racist behaviour as a bystander. Subsequently, they were asked to respond to a series of open and closed questions. Quantitative findings suggested that knowledge on how to act was predicted by confidence and responsibility; responsibility was predicted by ethnicity (being non-mestizo), confidence, noticing the event, and feeling more uncomfortable; and confidence was predicted by noticing the event, feeling less uncomfortable and more responsible. In the analysis of the qualitative data, we identified six themes. These were (i) Bystander characteristics and circumstances; (ii) Bystander morality and attitudes towards racism; (iii) Clarity of the situation; (iv) Perceived need and deservedness; (v) Presence of authorities and other people, and (vi) Consequences of action: Safety to the bystander. We discuss these findings in relation to racism in the Colombian context.